"A dying vibration": Sound and Silence in Heart of Darkness. (16th January 2017) - Rawson, Eric
Abstract : Conrad's jarring juxtapositions of sound and silence in Heart of Darkness emphasize the epistemological and ontological concerns of a narrative the stands at the threshold of the modern information age, in which the sounds of the world are being rapidly reorganized into an electroacoustical coding and decoding of information that collapses traditional notions of the communicative availability of the aural. While not as immediately engaging as the novel's fraught visual imagery, the soundscape of Heart of Darkness shapes Marlow's – and the reader's – understanding of his African journey.